Penerapan Relaksasi Autogenik Terhadap Masalah Keperawatan Manajemen Kesehatan Keluarga Tidak Efektif Pada Lansia Dengan Hipertensi - Zahara Aulia, Ananda; Ezalina; Saputra, Candra; Drisposwana, , Ifon (Jurnal Keperawatan Muhammadiyah, 2025)
Introduction: Elderly is someone who has reached the age of 60 years and above. Elderly hypertension occurs due to the aging process, one of which is characterized by a decrease in the elasticity of the aortic wall, thickened and stiffened heart valves, a decrease in the heart's ability to pump blood, so that blood pressure increases. The purpose of the Ners Final Scientific Work is to provide an overview of the results of Ners Professional practice with the Application of Family Nursing Care with the Application of Autogenic Relaxation Therapy to Nursing Problems of Ineffective Family Health Management in the Elderly with Hypertension in Sungai Putih Village tapung sub-district, kampar district. The method used in the implementation of nursing interventions is the provision of Autogenic relaxation therapy to patients with hypertension. The author started on February 17-22, 2025. The advantages of Autogenic relaxation therapy are its ability to reduce pressure, reduce muscle tension, lower heart rate, change fat levels in the body, and reduce the inflammatory process. Relaxation methods provide benefits to the brain, namely increasing alpha waves so as to create a calm and fresh state and improve focus. The implementation of Autogenic relaxation therapy was carried out for 2 days for 15 minutes. The results of this case study after 2 days of the subject applying Autogenic relaxation therapy showed that on average after being given there was a significant difference in family success in the recommended activities before and after being given Autogenic relaxation and there was a significant difference between pain intensity before and after autogenic relaxation therapy in the elderly with hypertension.